Employees and corporate governance (Washington, DC, 1999)
"Most scholarship on corporate governance in the last two decades has focused on the relationships between shareholders and managers or directors. Neglected in this vast literature is the role of employees in corporate governance. Yet "human capital," embodied in the employees, is rapidly becoming the most important source of value for corporations, and outside the United States, employees often have a significant formal role in corporate governance. This volume turns the spotlight on the neglected role of employees by analyzing many of the formal and informal ways that employees are actually involved in the governance of corporations, in U.S. firms and in large corporations in Germany and Japan. Examining laws and contexts, the essays focus on the framework for understanding employees' role in the firm and the implications for corporate governance. They explore how and why the special legal institutions in German and Japanese firms by which employees are formally involved in corporate governance came into being, and the impact these institutions have on firms and on their ability to compete. They also consider theoretical and empirical questions about employee share ownership."